Microbial Iron(II) Oxidation in Littoral Freshwater Lake Sediment: The Potential for Competition between Phototrophic vs. Nitrate-Reducing Iron(II)-Oxidizers - Melton, Emily Denise; Schmidt, Caroline; Kappler, Andreas (Frontiers in Microbiology, 2012)
The distribution of neutrophilic microbial iron oxidation is mainly determined by local gradients of oxygen, light, nitrate and ferrous iron. In the anoxic top part of littoral freshwater lake sediments, nitrate-reducing and phototrophic Fe(II)-oxidizers compete for the same e- donor; reduced iron. It is not yet understood how these microbes co-exist in the sediment and what role they play in the Fe cycle. We show that both metabolic types of anaerobic Fe(II)-oxidizing microorganisms are present in the same sediment layer directly beneath the oxic-anoxic sediment interface. The photoferrotrophic MPNs counted 3.4•105 cells•g-1 and the autotrophic and mixotrophic nitrate-reducing Fe(II)-oxidizers totalled 1.8•104 and 4.5•104 cells•g-1 dry weight sediment, respectively. To distinguish between the two microbial Fe(II) oxidation processes and assess their individual contribution to the sedimentary Fe cycle, littoral lake sediment was incubated in microcosm experiments. Nitrate-reducing Fe(II)-oxidizing bacteria exhibited a higher maximum Fe(II) oxidation rate per cell, in both pure cultures and microcosms, than photoferrotrophs. In microcosms, photoferrotrophs instantly started oxidizing Fe(II), whilst nitrate-reducing Fe(II)-oxidizers showed a significant lag-phase during which they probably use organics as e- donor before initiating Fe(II) oxidation. This suggests that they will be outcompeted by phototrophic Fe(II)-oxidizers during optimal light conditions; as phototrophs deplete Fe(II) before nitrate-reducing Fe(II)-oxidizers start Fe(II) oxidation. Thus, the co-existence of the two anaerobic Fe(II)-oxidizers may be possible due to a niche space separation in time by the day-night cycle, where nitrate-reducing Fe(II)-oxidizers oxidize Fe(II) during darkness and phototrophs play a dominant role in Fe(II) oxidation during daylight. Furthermore, metabolic flexibility of Fe(II)-oxidizing microbes may play a paramount role in the conservation of the sedimentary Fe cycle.